Quantitative Susceptibility Mapping and Vessel Wall Imaging as Screening Tools to Detect Microbleed in Sentinel Headache - Ishii, Daizo; Nakagawa, Daichi; Zanaty, Mario; Roa, Jorge A.; Al Kasab, Sami; Shaban, Amir; Hudson, Joseph S.; Osorno-Cruz, Carlos; Byer, Stefano; Allan, Lauren; Torner, James C.; Awad, Issam A.; et al. (Journal of clinical medicine, 2020)
Background: MR-quantitative susceptibility mapping (QSM) can identify microbleeds (MBs) in intracranial aneurysm (IA) wall associated with sentinel headache (SH) preceding subarachnoid hemorrhage. However, its use is limited, due to associated skull base bonny and air artifact. MR-vessel wall imaging (VWI) is not limited by such artifact and therefore could be an alternative to QSM. The purpose of this study was to investigate the correlation between QSM and VWI in detecting MBs and to help develop a diagnostic strategy for SH. Methods: We performed a prospective study of subjects with one or more unruptured IAs in our hospital. All subjects underwent evaluation using 3T-MRI for MR angiography (MRA), QSM, and pre- and post-contrast VWI of the IAs. Presence/absence of MBs detected by QSM was correlated with aneurysm wall enhancement (AWE) on VWI. Results: A total of 40 subjects harboring 51 unruptured IAs were enrolled in the study. MBs evident on the QSM sequence was detected in 12 (23.5%) IAs of 11 subjects. All these subjects had a history of severe headache suggestive of SH. AWE was detected in 22 (43.1%) IAs. Using positive QSM as a surrogate for MBs, the sensitivity, specificity, positive predictive value, and negative predictive value of AWE on VWI for detecting MBs were 91.7%, 71.8%, 50%, and 96.6%, respectively. Conclusions: Positive QSM findings strongly suggested the presence of MBs with SH, whereas, the lack of AWE on VWI can rule it out with a probability of 96.6%. If proven in a larger cohort, combining QSM and VWI could be an adjunctive tool to help diagnose SH, especially in cases with negative or non-diagnostic CT and lumbar puncture.